If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + 1) = 40 Reorder the terms: 4(1 + y) = 40 (1 * 4 + y * 4) = 40 (4 + 4y) = 40 Solving 4 + 4y = 40 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4y = 40 + -4 Combine like terms: 4 + -4 = 0 0 + 4y = 40 + -4 4y = 40 + -4 Combine like terms: 40 + -4 = 36 4y = 36 Divide each side by '4'. y = 9 Simplifying y = 9
| .75x+1.5=2.7 | | 2m+3(m+2)=13 | | 5n-4+2n=17 | | 10z=8a+5a-3a | | 4(6x+10)=112 | | 15x+(-3x)+7x+4= | | x=x-2 | | 2t+(-6t)-6=2 | | 7n-4+9n=28 | | 17=24-y | | 3x+10x+2=92 | | 3n-n+7=13 | | .25q=10 | | 5n-8+n=4 | | 19xy(x+y)= | | 4w-8=16 | | 7x-5=6x+9 | | 3x+12x= | | 3n+2n+5=20 | | 3x=12x | | x=(x-2)*(x+6) | | 20+8n=60 | | 8k(4k-4)=-5k | | 16=.05r-8 | | 18x^2+33x-21=0 | | 3.50v=31.5 | | 2x+(-x+5)=11 | | 3(w+1)-6w=18 | | 16=4+3x | | 4-3x=-3 | | 62+(b-18)=86 | | -2(a+3)-a=0 |